Evoked potentials in patients with lumbar spine stenosis - E. G. Ippolitova; T. K. Verhozina; Z. V. Koshkareva; V. A. Sorokovikov; N. I. Arsentyeva (Acta Biomedica Scientifica, 2015)
As the results of complex examination of patients with compressive syndromes accompanied by spinal stenosis we determined main factors and types of compression of spinal cord roots. We analyzed electroneuromyography of 64 patients who had in their anamnesis osteochondrosis of the 2-3rd gestation period complicated with diskogenic lumbosacral radiculitis with clinical and neurological manifestation and pain syndrome of different severity level. It was established that demyeliniation is accompanied with segmental disorders expressed in the deficiency of supraspinal and suprasegmental influences that manifested as a result of ischemic process of conduction tract of spinal cord at the stenosis. Decrease of the range of reflex response (H-reflex) and afterpotential (F-wave) or their fallback is possibly connected with hypostasis of the root without its local demyeliniation. Increase of latent period of H-reflex and F-response and also band broadening of the rate of conduction of excitation correspond to the moderate changes at the pathology of proximal segment of the nerve that is the sign of local demyeliniation of the root at the absence of peripheral axonopathy. Expressed disorders correspond to the dissociation of impulse conduction velocity on the proximal segment and to the signs of axonal neuropathy of distal segment of neuromotor apparatus. Thus, the changes of such electroneuromyographic indices as impulse conduction velocity and inflammability that correspond to the manifestations of L-spinal stenosis of are caused by the compression of roots and their vessels both on injured and intact limb with development of their ischemia. Rate of conduction of excitation significantly decreases at demielinising processes caused by stenosis. Obtained data allows the clinicians to develop adequate and pathogenetically caused scheme of treatment of patients with spinal stenosis.